Penerapan Sistem Manajemen Rekam Web pada DPMPTSP Kota Samarinda dengan Menggunakan Framework Laravel - Mohammad Hiqmal Fiqri; Wawan Joko Pranoto; Bayu Gaung Oktio Putra; Muhammad Nur Irvan; Wahyu Laksana (Jurnal Publikasi Teknik Informatika, 2024)
The management of physical archives into digital formats is a crucial aspect in enhancing the operational efficiency of government agencies, particularly the DPMPTSP of Samarinda City. This research proposes and implements a web-based record management system using the Laravel framework to facilitate this process. The primary focus is to simplify employees' tasks in transforming and managing archives digitally, reducing dependence on physical archiving that often consumes time and resources. Laravel framework is chosen for its reliability in web development and ease of integration with other technologies.The implementation of this system not only transforms how employees store archives but also streamlines the file borrowing process. The system allows employees to easily search for and borrow archives electronically, overcoming traditional barriers in information retrieval. The implementation results show a significant improvement in archive management efficiency, creating an innovative and relevant solution to administrative challenges in government agencies. The success of this implementation creates opportunities to further modernize public administration processes, making technology utilization a key factor in improving productivity and service quality. Thus, this research makes a positive contribution to the transformation of public administration through technology implementation, paving the way for more effective and integrated archive management.